UNASUR’S IDENTITY: POST-NEOLIBERAL OR POST-HEGEMONIC REGIONALISM? - Falomir Lockhart, Nicolás (2013)
Since the new millennium, a new process of regional integration is being built in South America. However, due to its particularities it is a process that cannot be explained by the pre-existing models of integration. Therefore, many conceptualizations have been proposed, such as post-neoliberal regionalism or post-hegemonic regionalism. Yet, none of them has reached a successful synthesis of the South American phenomenon.